(untitled) (Homoeopathy for All, 2024)
Drug-induced liver injury (DILI), a significant concern in modern medicine, is commonly caused by hepatotoxic medications such as acetaminophen (Paracetamol). It can manifest as either acute or chronic liver damage, leading to symptoms like jaundice, fatigue, abdominal pain, nausea, and alterations in urine and stool color. While conventional treatments for DILI focus primarily on the withdrawal of the offending drug and supportive care, these approaches are often insufficient, as there are limited specific antidotes available for most cases. This necessitates the exploration of non conventional treatment options like homeopathy to address the root causes of DILI effectively. Acetaminophen, the most frequent cause of DILI, has been widely studied for its hepatotoxic effects. Research has shown that homeopathic drugs like Carduus marianus and Chelidonium majus, with their potential to prevent paracetamol induced centrilobular necrosis, vacuolization & macro-vesicular fatty changes, inflammation, and elevated serum markers like SGOT, SGPT, bilirubin, etc., may offer significant hepatoprotective benefits. These remedies work by counteracting macromolecular